Building Paradigms: Major Transformations in School Architecture (1798-2009) - Gislason, Neil (Alberta Journal of Educational Research, 2010)
This article provides an historical overview of significant trends in school architecture from 1798 to the present. I divide the history of school architecture into two major phases. The first period falls between 1798 and 1921: the modern graded classroom emerged as a standard architectural feature during this period. The second period, which extends from 1921 to the present, has been defined primarily by the growing influence of progressive educational ideas and practice on school design. It is argued that school architecture has changed gradually over the last 200 years by building on existing design trends rather than breaking from them. The article concludes with some speculations about current trends in school architecture.